The effects of board attributes on Sukuk rating - Elhaj M.A.; Muhamed N.A.; Ramli N.M. (Emerald Group Publishing Ltd., 2024)
Purpose: The purpose of this paper is to investigate the effect of board attributes on Sukuk rating in firms listed in Bursa Malaysia (Malaysian Stock Exchange) during the period of 2008 to 2013. Design/methodology/approach: This study uses ordinal logit regression model to examine the influence of board attributes (CEO-chairman duality, board size and board independence) on the dependent variable (RATING). Findings: The findings of this paper generally support the agency theory and stakeholder theory. Results show that after controlling for firm characteristics, the Sukuk rating is positively associated with CEO-chairman duality, board size and board independence; and negatively correlated with leverage while positively related to profitability and size. The findings of this study also provide evidence that having two positions in an organization as CEO and chairman could have added higher responsibility towards making corporate decisions and provide better Sukuk rating performance. In addition, findings show that the larger the board size, the better Sukuk rating. Also, higher board independence enjoys higher rating. Research limitations/implications: This study was limited to the investigation of the relationship between board attributes (CEO duality, board size and board independence) on Sukuk ratings using aggregate data from 2008 to 2013 among Malaysian Sukuk issuers. Practical implications: The findings of this paper describe the impact of board attributes on Sukuk rating in Malaysian Sukuk market which in turn gives the useful insights to many of the actors in the markets such as issuers, investors and policymakers which can be relied upon in making strategic decisions to issue and invest in Islamic bonds in Malaysian market. In addition, the findings could prove to be useful also for regulators because they are responsible for the acceptable level of corporate governance standards. Originality/value: This study contributes to the body of knowledge by focusing heavily on enhancing Sukuk ratings by reducing conflict between managers and Sukuk holders in Malaysia. Additionally, this study benefits from the agency theory and stakeholder theory to provide evidence on the effect of board attributes on Sukuk rating. 2018, Emerald Publishing Limited.